Analysis of Non-Performing Credit Settlement at PT. Bank NTB Syariah - Nurul Hidayati Indra Ningsih Nurul; Baiq Reinelda Tri Yunarni; Mos Indrawati; Nur Lia; Artika Widiandari; Ersa Wahyuliati; Nurul Huda (Jurnal Economic Resource, 2023)
This study aims (1) to analyse the factors that cause problem financing at PT Bank NTB Syariah (2) to find out how to solve problem financing at PT Bank NTB Syariah (3) to find out what are the obstacles to solving problem financing at PT Bank NTB Syariah. This type of research uses qualitative research. The data collection method used in this research is the interview method. Checking the validity of the findings using source triangulation so that it is easy to analyse various problems that occur at Bank NTB Syariah. The results of the study, (1) There are 2 factors that cause problem financing, namely, external factors and internal factors from customers (2) Efforts made by PT. Bank NTB Syariah in solving Problem Financing, namely: Doing billing by telephone media, Short Message Service (SMS) and WhatsApp, using very polite and smooth language, considering it as customer service, increasing intensive hospitality with customers, transferring customers, restructuring financing, collateral auctions by submitting the Customer's collateral auction process to the KPKLN. The last step is insurance claims and write-offs.